IMPLEMENTING THE VALUES OF PEACE AND A CHAMPIONSHIP ATTITUDE IN FORMING THE CHARACTER OF STUDENTS FOR TKA-TPA AMM KOTAGEDE YOGYAKARTA - Nidaul Fajrin; Syahrul Fauzi; Subiyantoro Subiyantoro; Mufthi Alam; Muhammad Ghozali (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
This study aims to determine the instilling of peaceful values and attitudes of champions in early childhood. This study uses a qualitative-descriptive approach housed in TKA-TPA AMM Kotagede Yogyakarta, data collection techniques performed by observation, interviews, and documentation. The results of this study indicate that the instilling of peace values starts from something small, such as making peace in the classroom. Indeed, with tranquility, there will be a sense of peace. Hence, there is the term “needle falls sound”. Communicate using great language and gentle intonation to anyone and appreciate the person speaking in front of the class. The effort to instill a champion attitude in students TKA-TPA AMM by giving a star writing on the board for students who dare come forward to memorization that has been given by the teacher. The next effort is to give applause to students who have dared to show up in front of the class so that other students are triggered and enthusiastic to show up. Conducting evaluations every month aims to determine student achievement and their ability limits and hold a final Semester assessment (PAS) as one of the reports from the institution to the Guardians of students.